Electrocardiographic Changes in Newly Diagnosed Primary Hypothyroidism: An Observational Study - Khatri, Prabin; Sapkota, Suman Raj; Gami, Sumit; Upadhyaya, Ashutosh; Alam, Mohammad Rizwan; Maharjan, Shristi; Upadhyaya, Shriya; Panth, Himal; Maskey, Sameer; Neupane, Aryan (Journal of Karnali Academy of Health Sciences, 2021)
Background: The thyroid hormones have an important role in the cardiovascular system; even minimal change in its level can cause significant alteration in the cardiac activity which can cause considerable electrocardiographic changes. We conducted this study to assess the electrocardiographic (ECG) changes in patients who were newly diagnosed with primary hypothyroidism. Methods: This study is a descriptive cross-sectional study conducted among 71 newly diagnosed subclinical and overt primary hypothyroidism patients visiting the out-patient department (OPD) of Universal College of Medical Sciences, Nepal from December 2018 to June 2020 after taking ethical clearance from the institutional review committee (UCMS/IRC/212/18). ECG was obtained for each patient at the time of diagnosis of primary hypothyroidism. The data were analyzed with SPSS Version 16. Results: The most common ECG changes were sinus bradycardia seen in 32.4%, followed by T wave inversion in 21.1%, low voltage QRS complex in 15.5%, and prolonged PR interval in 14.1%. ECG changes were seen in 62% of cases of newly diagnosed primary hypothyroidism. Among all patients, subclinical hypothyroidism accounted for 7%, while overt hypothyroidism accounted for 55% of the ECG findings. Conclusion: Our study found ECG changes like sinus bradycardia, T wave inversion, low QRS voltage, and prolonged PR interval in newly diagnosed primary hypothyroidism. We suggest that every newly diagnosed hypothyroid patient should be evaluated for ECG changes.